A tribo Phaseoleae s.l. (Leguminosae-Papilionoideae) no município de Caetité, Estado da Bahia, Brasil - Teixeira, Jaqueline Dias; Ferreira, Jamile Jorge Da Silva [UNESP]; Silva, Juliana Santos (Instituto de Pesquisas Ambientais, 2021)
(The tribe Phaseoleae s.l. (Leguminosae-Papilionoideae) in the municipality of Caetité, Bahia State, Brazil). Phaseoleae s.l. comprises the largest tribe of subfamily Papilionoideae in number of genera, with 89 genera and 1,567 species. Regional taxonomic studies of the tribe are only occasional in Brazil and rare in Northeastern Brazil, including Bahia, the region’s most species-rich state. In this context, the present study had as its objective to carry out a taxonomic study of the species of Phaseoleae s.l. occurring in Caetité (BA), a conservation priority region for the Caatinga vegetation. For this purpose, we made field expeditions and visited to the HUNEB-Collection Caetité and HUEFS Herbaria. A total of 25 species and 15 genera were recorded, accounting for 23% of the species registered for Bahia. Caetité stands out as one of the main centers of floristic richness of Phaseoleae s.l. in the semi-arid region of Bahia state. Leaflet shape, inflorescence type and the coloration of the petals and seeds are the most useful characters for identification.

(A tribo Phaseoleae s.l. (Leguminosae-Papilionoideae) no município de Caetité, Estado da Bahia, Brasil). Phaseoleae s.l. é a maior tribo de Papilionoideae em número de gêneros, com 89 e 1.567 espécies. Os estudos taxonômicos regionais da tribo são pontuais no Brasil e raros no Nordeste do Brasil, incluindo a Bahia, o Estado mais rico em espécies da região. Neste contexto, este trabalho teve como objetivo realizar o tratamento taxonômico das espécies de Phaseoleae s.l. ocorrentes em Caetité (BA), uma região de prioridade de conservação para a vegetação de Caatinga. Para tanto, foram realizadas expedições de coleta e visitas aos Herbários HUNEB-Coleção Caetité e HUEFS. Um total de 25 espécies e 15 gêneros foi registrado, o que representa 23% das espécies registradas para a Bahia. Caetité destaca-se como um dos principais centros de riqueza florística de Phaseoleae s.l. no semiárido baiano. O formato dos folíolos, tipo de inflorescência e a coloração das pétalas e das sementes são os caracteres mais úteis na identificação dos táxons.
Keywords: biodiversity; ecotone; Fabaceae; flora; plant taxonomy; biodiversidade; ecótono; Fabaceae; flora; taxonomia vegetal